2008
DOI: 10.1111/j.1471-0528.2008.01773.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting adequacy of Pipelle and Tao Brush endometrial sampling

Abstract: Objective To compare factors influencing adequacy of endometrial samples obtained using two outpatient sampling devices -Pipelle and Tao Brush.Design Pragmatic unblinded trial with investigation schedule randomised separately within two groups according to endometrial cancer risk.Setting Gynaecology outpatient clinic of a large city hospital in Edinburgh, Scotland.Population All women referred to a gynaecology outpatient clinic during a 28-month period complaining of abnormal vaginal bleeding.Methods Women wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 22 publications
(30 reference statements)
3
72
1
3
Order By: Relevance
“…Different authors report a percentage of non-diagnostic examinations of between 3 and 16% [13,[16][17][18]. In their meta-analysis Dijkuzen et al estimated that 10.4% of pipelle biopsies involve ineffective sampling of uterine cavity material [4].…”
Section: Discussionmentioning
confidence: 99%
“…Different authors report a percentage of non-diagnostic examinations of between 3 and 16% [13,[16][17][18]. In their meta-analysis Dijkuzen et al estimated that 10.4% of pipelle biopsies involve ineffective sampling of uterine cavity material [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, in randomized trials from Scotland, the Tao Brush (Cook Medical; Bloomington, IN; USA) was found to be superior to the Pipelle catheter in obtaining a satisfactory endometrial sample (72% to 43%) 56,57 (Class 1b). Endometrial cytology with liquid-based techniques has also been described to have a high sensitivity for carcinoma, but it has not been compared with blind sampling 58 (Class 3).…”
Section: Investigation Of Women With Postmenopausal Uterine Bleeding:mentioning
confidence: 99%
“…In meta-analysis the reported range of sampling failure was 0 to 58% with pipelle endometrial sampling [16]. Two studies confirmed a high failure rate (51% and 64%, of which 30% and 48% were insufficient samples) [17,18]. Malignancy cannot be excluded in women with insufficient ES [19,20], and HY is often added.…”
Section: Discussmentioning
confidence: 72%